The Impact of Decentralized Finance on the Activities of Traditional Financial Intermediaries - M. T. Belova; I. A. Rizvanova (Финансы: теория и практика)
Over the past decade, digitalization, which has become a key driver of innovation in the financial industry, has led to the development of new products and financial services. The services and opportunities provided in the field of decentralized finance have similar characteristics to traditional financial services. The lack of sufficient experience in the functioning of the decentralized finance sphere determines the relevance of the study of the content and problems of the development of this format of financial organization. The object of study is the relations arising in the process of providing financial services in traditional and decentralized finance. The subject of the study is the impact of decentralized finance on the activities of traditional financial intermediaries. The purpose of the study is to determine the aspects of the impact of decentralized finance on the activities of traditional financial intermediaries. The objectives are to study the theory of trust in relation to decentralized finance, identify problems of their development, assess the challenges and prospects for the impact of decentralized finance on the activities of traditional financial intermediaries. The authors use general scientific and special methods, including system, comparative analysis, generalization, scientific abstraction. The scientific novelty of the study lies in a comprehensive assessment of the impact of decentralized finance on the activities of traditional financial intermediaries through the prism of the capabilities of the decentralized finance system at the current stage of financial market development. The authors conducted a study of the theory of trust in relation to decentralized finance, and also proposed forms of ensuring trust in financial services provided in the traditional (TradFi) and decentralized financial systems (DeFi). To assess the challenges and prospects of decentralized finance and their impact on the activities of traditional financial intermediaries, a PEST analysis was conducted, identifying groups of political, economic, technological and socio-cultural factors of influence. It is concluded that the influence of the decentralized finance sphere on the activities of traditional financial intermediaries will expand due to the increase in the market capitalization of DeFi and the spread of systemic risks characteristic of TradFi. Focus on minimizing risks should facilitate the use of DeFi services by traditional financial intermediaries in the context of creating and developing innovative projects. The conducted research can be useful both for users of traditional and decentralized finance services and for regulatory and supervisory authorities.